ChemInform Abstract: Direct Trifluoromethylthiolation of Unactivated C(sp3)—H Using Silver(I) Trifluoromethanethiolate and Potassium Persulfate. Issue 31 (August 2015) - Wu, Hao; Xiao, Zhiwei; Wu, Junhui; Guo, Yong; Xiao, Ji‐Chang; Liu, Chao; Chen, Qing‐Yun
Abstract The trifluoromethylthiolation of unactivated C—H bonds is proposed to involve a radical process in which potassium persulfate shows key behavior in both the activation of the C—H bond and the oxidation of the silver reagent.